1982
DOI: 10.1113/expphysiol.1982.sp002612
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Role of a Slow, Voltage‐sensitive, Synaptic Response Mediated by an Identified Serotonin‐containing Neurone

Abstract: SUMMARYIn Helix, activation of an identified serotonin-containing neurone produces a slow, markedly voltage-sensitive, depolarizing synaptic potential in another identified neurone, the A neurone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Our results suggest that the mechanism of this facilitation is more general in that NA makes the cell more responsive to any excitatory stimulus by blocking the cell's intrinsic inhibitory GK(ca). This action is similar in many ways to excitatory effects reported in other systems such as serotonergic excitation of myenteric neurones (Grafe et al 1980) or activation of a presynaptic serotonergic neurone on a follower neurone in Helix (Cottrell, 1982).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results suggest that the mechanism of this facilitation is more general in that NA makes the cell more responsive to any excitatory stimulus by blocking the cell's intrinsic inhibitory GK(ca). This action is similar in many ways to excitatory effects reported in other systems such as serotonergic excitation of myenteric neurones (Grafe et al 1980) or activation of a presynaptic serotonergic neurone on a follower neurone in Helix (Cottrell, 1982).…”
Section: Discussionmentioning
confidence: 63%
“…is that NA is not the only neurotransmitter that has this action. Acetylcholine (Benardo & Prince, 1982;North & Tokimasa, 1983;Cole & Nicoll, 1984), serotonin (Grafe et al 1980, Cottrell, 1982, histamine (Haas & Konnerth, 1983) and corticotropin releasing factor (Aldenhoff, Gruol, Rivier, Vale & Siggins, 1983) all decrease calcium-activated potassium a.h.p.s in various neuronal preparations. That such a diverse array of putative neurotransmitters can block this potassium conductance, and that this blockade has such a profound effect on the responsiveness of the affected neurone, implies strongly that the calcium-activated potassium channel plays a central role in the regulation of neuronal excitability, and indeed that it may serve as a final common path for the actions of many neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…Accompanying the voltage-dependent response in Helix is a broadening of the action potential (Cottrell, 1982;Paupardin-Tritsch, DeTerre, and Gerschenfeld, 1981) similar to that reported by Klein and Kandel (1978) in sensory neurons of Aplysia. Klein and Kandel (1980) have suggested that the mechanism underlying this serotonin-elicited spike broadening is a decrease in potassium conductance.…”
Section: Introductionmentioning
confidence: 82%
“…The response began to occur at about the same potential at which the delayed rectification was activated. The ionic mechanism of this response was studied by Cottrell (1982 a), and therefore only a summary of those results previously described will be given here, along with results from some additional experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The present report describes the effects of FMRFamide, and of two homologous peptides, Phe-Nle-Arg-Phe-NH2 (FnLRFamide) and Tyr-Gly-Gly-Phe-Met-Arg-Phe-NH2 (YGGFMRFamide), on a number of different specified neurones in the ganglia of Helix aspersa. Some of this work has been published in abstract (Cottrell, 1982 a). METHODS Experiments were made on identified neurones in the cerebral, visceral and right parietal ganglia of Helix asper8a.…”
Section: Introductionmentioning
confidence: 99%